Comparison of patients with chronic and episodic migraine with healthy individuals by brain volume and cognitive functions - Kamacı Şener, Deniz; Zarifoğlu, Mehmet; Hakyemez, Bahattin; Karlı, Necdet; Türkeş, Nevin (The European Research Journal, 2025)
Objectives: Migraine is a complex neurological disease. In addition to headache, individuals with migraine may develop structural changes inside the brain and cognitive impairment. There is increased evidence associated with impairments in brain volume and cognitive functions in patients with migraine. The present study aimed to investigate the impairment in memory function in individuals with migraine using brain magnetic resonance imaging, volume measurement, and neuropsychological tests. Methods: The study included 20 patients with episodic migraine, 20 patients with chronic migraine, and 20 healthy controls. Subcortical volumes of all participants were measured by FreeSurfer, an automatic segmentation method. The Wechsler Memory Scale-Revised Form (WMS-R), Stroop test, Raven’s Standard Progressive Matrices, Verbal Fluency Test, and Lines Orientation Test were applied in all the study participants. Results: Putamen volume decreased as migraine duration increased, and subcortical gray matter, left cerebellar cortex, and bilateral thalamus volumes were lower in the chronic and episodic group compared to the control group, bilateral putamen and right cerebellar cortex volumes were lower in patients with chronic migraine compared to patients in episodic migraine and control groups. Upon neuropsychological examination, delayed memory was affected as the duration of migraine increased, and there was impairment in patients with chronic migraine upon fluency tests and mental control tests. Conclusions: Changes in subcortical volume and cognitive effects in patients with migraine raise questions about whether migraine qualifies as a benign disease. Structural changes and cognitive impairment may contribute to migraine-associated disability, and therefore, these causalities should be investigated by future studies. Silent infarcts, white matter damage, and cortical spreading depression, which occur in migraine cases, may be associated with subcortical volume changes and thus, cognitive effects. In the context, studies with larger samples to achieve a better understanding are needed.